FIRM DISCOURSES AND DIGITAL INFRASTRUCTURE PROJECTS - O'Neil, Mathieu; Muselli, Laure; Zacchiroli, Stefano; Cai, Xiaolan; Pailler, Frederic (AoIR Selected Papers of Internet Research, 2020)
Free and open source software (a.k.a. FOSS or ‘digital infrastructure’) is now fully integrated into commercial ecosystems. IT firms invest in FOSS in order (a) to share with other firms development costs; (b) to help attract prospective employees in a competitive job market where hiring skilled IT professionals is challenging and (c) to shape the governance and technical orientation of projects: firm employees participating in leading in FOSS projects may help IT firms create digital infrastructure more suited to the firmware they develop atop this infrastructure. How does the world of FOSS volunteers connect to the world of commercial ecosystems? Are firms developing policies in relation to open source communities, requesting projects conform to certain technical or behavioral standards, for example? To what extent are these strategies successful? To answer, we present a qualitative analysis of firm discourses collected during three open source conferences. We then analyze the email discussion lists of Linux and Firefox and search for the occurrence of key firm discourse terms in order to ascertain in what way these discourses are being used by FOSS developers. Our in-depth analysis of firm discourses and exploratory analysis of project discussions around these terms show that the FOSS world encompasses a diversity of industrial outlooks. They also highlight the evolution of the role of foundations: whilst foundations used to protect projects from firm interference, some have now wholly been placed in the service of firm efforts to standardize project work, particularly around the key issue of security.